Optimization Analysis of Pretreatment Device Structural Parameters for Low-Concentration CBM Utilization - Lu Xiao (Geofluids)
The unstable concentration of the difficulty in utilizing low-concentration CBM causes a large amount of CBM to be discharged into the atmosphere. In order to ensure the safe and stable operation of the CBM utilization device, the gas mixing unit is used to stabilize the concentration of feed gas. Generally, the resistance of the gas mixing unit is not higher than 500 Pa and the uniformity of gas is not less than 90%. In order to solve the problems of heavy resistance and low uniformity of the existing CBM mixing unit, a three-dimensional calculation model is established, and the structural parameters such as the number of spiral blades, blade length, and pitch in the gas mixing unit are adjusted and verified by experiments to achieve optimal performance. The dimensionless mathematical correlation between the resistance loss and the uniformity of gas is refined, and the maximum error between the resistance loss and the simulation results is controlled within 10%; it provides a theoretical basis for the uniformity and low resistance mixing of different gases in the gas industry. When the flow is 7000 Nm3/h, 50000 Nm3/h, and 160000 Nm3/h, respectively, the optimal structural parameters of the mixing zone are as follows: the number of blades is 3, 3, and 2, respectively, the pitch is 1000 mm, 2000 mm, and 2636 mm, respectively, and the length of blades is 500 mm, 1600 mm, and 1845 mm, respectively. The optimal structural parameters of the small pipe area are as follows: the mixing device with a flow of 50000 Nm3/h is not equipped with blades, the number of blades of the other two devices is 4, the pitch is 1400 mm, and the length of blades is 700 mm.